Profit Sharing dalam Pengelolaan Rumah Makan “Padang” - Fauzi Solihin (The Winners, 2004)
Article discusses profit sharing in running a “Padang” restaurant. Profit sharing always increase sense of belonging every employee and  support  the   management   function.  It   can   beconcluded that profit sharing can motivated employee to increase working performance and increase sense of belonging and responsibility. It also can increase continuous improvement team work between employee.